Analisis Pengawasan Dewan Perwakilan Rakyat Daerah (DPRD) Medan terhadap Kinerja Pemerintah Kota Medan - Neng Siska; Marliyah Marliyah (LPPM IAI Nasional Laa Roiba Bogor, 2023)
Education is a long-term investment in order to fulfill Indonesia's future pattern of human life. First, education as a project meant to enhance the human body's intellectual potential through a teaching and learning procedure Second, education contributes to the formation of an ethnically diverse society through the transmission of the values it includes. Third, education is one of the guarantees of a better, more honorable existence. Education must develop and evolve in educational institutions in a better path in order to become an investment. The use of operational and strategic management in educational institutions is one of the theoretical ideas put forth. The management of educational institutions is anticipated to be able to direct and impact the quality of educational products/outcomes including curriculum, institutional management administration, and student affairs through these two theoretical notions.